Making Room for Growing Oriented FASnI3 with Large Grains via Cold Precursor Solution. (10th April 2021) - Cui, Danyu; Liu, Xiao; Wu, Tianhao; Lin, Xuesong; Luo, Xinhui; Wu, Yongzhen; Segawa, Hiroshi; Yang, Xudong; Zhang, Yiqiang; Wang, Yanbo; Han, Liyuan
Abstract: Tin halide perovskites are promising candidates for preparing efficient lead‐free perovskite solar cells due to their ideal band gap and high charge‐carrier mobility. However, the notorious rapid crystallization process results in the inferior power conversion efficiency (PCE) of tin perovskite solar cells (TPSCs). Here, a facile method is employed to manage this crystallization process by using cold precursor solution that raises the critical Gibbs free energy to slow down the nucleation rate, sparing both space and time for crystal growth. In this way, highly oriented FASnI3 films with micrometer‐scale grains are fabricated and an increase of 70 mV in the open‐circuit voltage is obtained for TPSCs. This method is compatible with other existed strategies such as additive engineering or the post‐treatment method. The best‐performing device that combines 0 °C precursor solution and post‐treatment method demonstrates a PCE of 12.11%. Abstract : The relationship between the temperature of the precursor and the crystallization process of FASnI3 is disclosed. Due to the suppressed nucleation rate and prolonged crystal growth in cold precursors, a large grain and highly oriented FASnI3 film is obtained, resulting in an efficiency of 9.46%. This facile method is compatible with other strategies, yielding an efficiency of 12.11% after post‐treatment.